EFEKTIVITAS PROGRAM PELAYANAN POSYANDU LANSIA DI PUSKESMAS TUNTANG KECAMATAN TUNTANG KABUPATEN SEMARANG - Dera Aisyah, Syalini; Yuniningsih, Tri; Djumiarti, Titik (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Posyandu Lansia is a puskesmas program with the target age of 60 years and over or the elderly. Services at Posyandu Lansia include checking daily activities, weighing, measuring height, health counseling, and simple laboratory tests. but in the implementation of Posyandu the elderly have not reached the target of visiting the elderly, so it is The purpose of this study was to analyze the effectiveness of the Posyandu Lansia Service Program at Puskesmas Tuntang Tuntang District Semarang Regency and to analyze the supporting and inhibiting factors. The method used in this research is descriptive qualitative with data collection techniques of observation, interview, and documentation. The phenomena used to determine the effectiveness of the program are program accuracy, program socialization, program objectives, and program monitoring. And to find out the driving factors and inhibiting factors of the program seen from environmental conditions, inter-organizational relationships, resources, and characteristics and implementing agents. The results showed that the Posyandu Lansia program was not effective because of the phenomenon of program socialization of cadre knowledge that was not good enough, then the phenomenon of program objectives had not achieved service coverage, then the phenomenon of program monitoring was good because there was supervision from the Tuntang Puskesmas. The advice given by the author is by improving the performance of cadres is the task of the Tuntang Health Center, Tuntang Health Center provides socialization and adds health workers.